Sheet Metal 2005 - Geiger, Manfred; Duflou, Joost R.; Kals, H.J.J.; Shirvani, Bez; Singh, U.P. (Trans Tech Publications Ltd, 2005)
Proceedings of the 11th International Conference on Sheet Metal 2005, held at the Friedrich-Alexander University Erlangen-Nürnberg, Germany, 08-08 April 2005. <br
Keywords: Aluminum (Al); Finite Element Model (FEM); Forming; Laser; Sheet Metal; Simulation; Welding